EKSPLORASI SEJARAH DAN PEMERINTAHAN KERAJAAN BATULOLONG DI KABUPATEN ALOR - Anastasia Laubela; Ariyance Maleipada, Anamalinda Fanmalay, Andry Makalbani, Halena Muna Bekata, Petrus Mau Tellu Dony (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the history and government of the Batulolong kingdom in Alor district. This study is a qualitative research method with an ethnographic approach. The methods used in this study are interviews and field observations. The results showed that the Batulolong Kingdom was established around 1800, led by the First King Karlau Kep. King Karlau Kep came from Lukabakeka, who then travelled to Kiraman Village and was appointed as the first king after taking a traditional oath by destroying the moko heirloom. The Batulolong Kingdom borders the kingdoms of Kolana, Kui, Alor and Ombay Strait. Since its establishment, the Batulolong Kingdom has been led by 21 kings. During the Swaparaja period, it was led by 10 ketemukungan. The Batulolong Kingdom experienced a change in status when it was transformed into the South Alor sub-district on 17 October 1963 according to the Governor's Decree of the NTT Provincial Head dated 20 July 1963 with Number Pem.66/1/32/1963.